Long-Term Comparative Evaluation of Acoustic Climate in Selected Schools Before and After Acoustic Treatment - Józef KOTUS; Maciej SZCZODRAK; Andrzej CZYŻEWSKI; Bożena KOSTEK (Archives of Acoustics, 2013)
The results of long-term continuous noise measurements in two selected schools are presented in the paper. Noise characteristics were measured continuously there for approximately 16 months. Measurements started eight months prior to the acoustic treatment of the school corridors of both schools. An evaluation of the acoustic climates in both schools, before and after the acoustic treatment, was performed based on comparison of these two periods of continuous measurements. The autonomous noise monitoring stations, engineered at the Multimedia Systems Department of the Gdańsk University of Technology were used for this purpose. Investigations of measured noise, especially its influence on hearing sense, assessed on ground of spectral analyses in critical bands, is discussed. Effects of occupational noise exposure, including the Temporary Threshold Shift simulation, are determined. The correlation of the above said measurement results with respective instantaneous noise levels is discussed, and concluding remarks are presented. Some additional indicators such as air pollution or video analysis aiming at the analysis of corridor occupancy are also measured. It should be remembered that excessive noise, or air pollution may be evidence of a dangerous event and may pose health risks.